Adhesion and Stab-resistant Properties of FDM-printed Polymer/Textile Composites - Siver Cakar; Andrea Ehrmann (Tekstilec, 2023)
Stab-resistant clothing has been used for centuries by soldiers. Today, it is also used by policemen and other people in dangerous jobs or situations. While chain-mail or metal inserts in protective vests are heavy and uncomfortable, lightweight and bendable alternatives are currently the subject of investigation. Special textile fabrics offer a certain level of stab-resistance that can be improved by different coatings. In this study, we investigated composites of different flexible 3D printing materials, used for the fused deposition modelling (FDM) technique, on woven fabrics. Besides the adhesion between both parts of these composites, the quasi-static stab-resistant properties were investigated and compared with those of pure textile fabrics and 3D prints, respectively.